The Influence Of Content Marketing and Influencer Marketing Strategies Through Perceived Quality on Fore Coffee Purchase Decisions in Jabodetabek - Pradita Kusuma Dewi; Supriadi Thalib (Journal Social Society, 2026)
The urgency of this research lies in understanding how content marketing and influencer marketing strategies influence Fore Coffee purchase decisions through perceived quality in the highly competitive coffee industry in Jabodetabek, thereby providing valuable insights for businesses to develop more effective and consumer-oriented marketing strategies. This study aims to analyze the influence of content marketing and influencer marketing on perceived quality and to examine the role of perceived quality in affecting consumer purchase decisions at Fore Coffee. The growth of digital media has positioned social platforms as a primary source of information in purchasing decisions, particularly within the modern coffee industry. Fore Coffee utilizes content marketing and influencer marketing strategies to shape consumers’ perceived quality and encourage purchasing decisions. Using a quantitative approach, data were collected through surveys from 204 respondents in the JABODETABEK region and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 4.0.9.9. The findings reveal that content marketing significantly influences perceived quality (t = 7.959; p < 0.05), while influencer marketing also has a significant effect on perceived quality (t = 1.972; p < 0.05). In addition, perceived quality significantly affects purchase decisions (t = 30.786; p < 0.05) and mediates the relationship between both marketing strategies and purchase decisions. These findings highlight the important role of perceived quality in strengthening the effectiveness of digital marketing strategies and provide practical insights for coffee businesses in optimizing consumer purchasing decisions.